2022
DOI: 10.1038/s41598-022-07980-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA- and RNA-based bacterial communities and geochemical zonation under changing sediment porewater dynamics on the Aldabra Atoll

Abstract: The remote Aldabra Atoll, Seychelles, provides the rare opportunity to study bacterial communities in pristine carbonate sediments across an entire biome. The four sampled sites cover sand with high porewater exchange, bioturbated silt and mud with intermediate exchange, as well as a seasonally and episodically desiccated landlocked pool. As sediments harbour dead cells and environmental DNA alongside live cells, we used bacterial 16S rRNA gene and transcript analysis to distinguish between past and present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(117 reference statements)
2
1
1
Order By: Relevance
“…Similar results were reported by Zinger et al (2011) , where Alphaproteobacteria was the dominant group in the pelagic communities, while Gammaproteobacteria was dominant in the benthic communities in the samples collected from the water column as well as the seafloor from the World’s oceans. However, it contrasts with the results obtained by Hoyningen-Huene et al (2022) , where a higher abundance of Alphaproteobacteria was detected from the sediment porewater from the Aldabra Atoll in Seychelles. Other abundant classes in the sediments include Bacilli, Actinobacteria and Acidimicrobiia.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Zinger et al (2011) , where Alphaproteobacteria was the dominant group in the pelagic communities, while Gammaproteobacteria was dominant in the benthic communities in the samples collected from the water column as well as the seafloor from the World’s oceans. However, it contrasts with the results obtained by Hoyningen-Huene et al (2022) , where a higher abundance of Alphaproteobacteria was detected from the sediment porewater from the Aldabra Atoll in Seychelles. Other abundant classes in the sediments include Bacilli, Actinobacteria and Acidimicrobiia.…”
Section: Discussioncontrasting
confidence: 99%
“…Microbial diversity in the sediments was found to decrease with an increase in depth from the seafloor. Similar results were obtained from the sediment porewater samples from the Aldabra Atoll, Seychelles where a decrease in phylogenetic diversity along with a shift in the microbial community was observed (Hoyningen-Huene et al, 2022). A higher abundance of Nitrosopumilaceae group of organisms can be related to their ammonia oxidizing potential in deep-sea sediments under aerobic conditions.…”
Section: Discussionsupporting
confidence: 83%
“…Foliar N:P ratio in our study was 11.7 ± 2.45 (Mean ± SD), suggesting mangroves in our study are N-limited, which is typical for fringe mangroves influenced by frequent tidal flushing 7,44 . N limitation at our study site is further indicated by the equally low N:P ratios documented in previous analyses on mangrove soil 45 and lagoonal sediment porewater on Aldabra 46 . At our seabird sites, uptake of seabird-derived nutrients alleviated mangrove nutrient limitations of both N and P, observed by reductions in foliar C:N and C:P ratios of R. mucronata .…”
Section: Discussionsupporting
confidence: 76%
“… 7 , 47 N limitation at our study site is further indicated by the equally low N:P ratios documented in previous analyses on mangrove soil 48 and lagoonal sediment porewater on Aldabra. 49 At our seabird sites, uptake of seabird-derived nutrients alleviated mangrove nutrient limitations of both N and P, observed by reductions in foliar C:N and C:P ratios of R. mucronata . Nutrient enrichment in N-limited mangroves can generate multiple higher order effects.…”
Section: Discussionmentioning
confidence: 65%